Intrathecally Administered D-Cycloserine Produces Nociceptive Behavior Through the Activation of N-Methyl-D-aspartate Receptor Ion-Channel Complex Acting on the Glycine Recognition Site - Koichi Tan-No; Akihisa Esashi; Osamu Nakagawasai; Fukie Niijima; Seiichi Furuta; Takumi Sato; Susumu Satoh; Hajime Yasuhara; Takeshi Tadano (Elsevier, 2007)
Intrathecal (i.t.) administration of D-cycloserine (100 and 300 fmol), a partial agonist of the glycine recognition site on the N-methyl-D-aspartate (NMDA) receptor ion-channel complex, produced a behavioral response mainly consisting of biting and/or licking of the hindpaw and the tail along with slight hindlimb scratching directed toward the flank in mice, which peaked at 5 - 10 min and almost disappeared at 15 min after the injection. The behavior induced by D-cycloserine (300 fmol) was dose-dependently inhibited by an intraperitoneal injection of morphine (0.5 - 2 mg/kg), suggesting that the behavioral response is related to nociception. The nociceptive behavior was also dose-dependently inhibited by i.t. co-administration of 7-chlorokynurenic acid (0.25 - 4 nmol), a competitive antagonist of the glycine recognition site on the NMDA receptor ion-channel complex; D-(−)-2-amino-5-phosphonovaleric acid (62.5 - 500 pmol), a competitive NMDA receptor antagonist; MK-801 (62.5 - 500 pmol), an NMDA ion-channel blocker; ifenprodil (0.5 - 8 nmol); arcaine (31 - 125 pmol); and agmatine (0.1 - 10 pmol), all being antagonists of the polyamine recognition site on the NMDA receptor ion-channel complex. However, [D-Phe7,D-His9]-substance P(6 - 11), a specific antagonist for substance P (NK1) receptors, and MEN-10,376, a tachykinin NK2-receptor antagonist, had no effect on D-cycloserine-induced nociceptive behavior. These results in the mouse spinal cord suggest that D-cycloserine-induced nociceptive behavior is mediated through the activation of the NMDA receptor ion-channel complex by acting on the glycine recognition site and that it does not involve the tachykinin receptor mechanism. Keywords:: D-cycloserine, N-methyl-D-aspartate (NMDA) receptor ion-channel complex, nociceptive behavior (mice), intrathecal administration